Alleviation of the V-Line rabbit bunnies' weaning stress by Moringa Oleifera incorporation with feed - Abdelghany, Asmaa K.; Maher, Mahmoud; Emeash, Hosny H.; Khalil, Fatma (Journal of Advanced Veterinary Research, 2023)
Raising rabbits has vital sustainable development features, as a sustainable development system of meat production strongly relies on its efficacy. The development system of meat production is correlated with the animals' capability for converting feed to meat. Weaning possess a marked stress on rabbits, because of lack of their normal caecal microbiota, hence young rabbits became more vulnerable to diseases. Numerous antibiotics alternatives have been successfully utilized, such as herbal medicines as natural supplements in animal feed. The leaves of Moringa Oleifera could potentially be utilized as a growth promoter due to their antimicrobial activity, antioxidant properties, hepato-protective effect, preservation of renal function, and hypocholesterolemic activity. Twelve recently weaned V-Line rabbit bunnies about four weeks of age and average body weight of 0.74 ± 0.07 were separated equally to feed either normal-prepared rabbit feed (Control group (C); n=6) or moringa-prepared feed (Moringa oleifera group (MO); n=6) for 4 weeks. Performance (feed intake, body weight, and weight gain), behavior, and serum biochemical analysis (oxidative stress, liver, and kidney function) were assessed. Results revealed that the incorporation of MO in recently weaned rabbit feed enhanced their performance and behavior, as well as lipid peroxidation and glutathione didn’t differ significantly and preserved liver and kidney function. In conclusion, MO plays a crucial role in weaning stress alleviation via their antioxidant, hepatic and renal function preservation and their positive effects on rabbit bunnies’ performance and behavior. Hence, the data suggests the use of MO leaves as a feed additive for rabbit bunnies to alleviate weaning stress.